A Brief Report Describing the Union of Medical Training and Agricultural Health. Issue 1 (2nd January 2016) - Levin, Jeffrey L.; Bowling, John; Wickman, Amanda J.; Harris, Michelle
ABSTRACT: This brief report describes a mutually beneficial partnership forged to extend agricultural medicine training to physicians, nurses, veterinarians, public health workers, health care professionals, medical residents, and students. Agricultural Medicine: Occupational and Environmental Health for Rural Health Professionals originated at the University of Iowa, Iowa's Center for Agricultural Safety and Health, and the Great Plains Center for Agricultural Health. Through a National Institute for Occupational Safety and Health (NIOSH)-funded Training Project Grant, The University of Texas Health Northeast worked with the University of Iowa and regional experts to adapt the agricultural medicine content for the southwestern United States. Further partnerships were developed with the Southwest Center for Agricultural Health, Injury Prevention and Education, The University of North Texas Health Science Center College of Osteopathic Medicine, and the Texas Rural Health Association to extend the reach of this training to other important stakeholders. Each of the collaborators offered unique resources to the coordination of the agricultural medicine course. Likewise, each organization benefited from extending regionally relevant agricultural medicine training to current and future health care providers. The long-term goal for the partnership is to train a broad array of health care providers with the basics of anticipation, recognition, diagnosis, treatment, and the prevention of occupational and environmental illnesses and injuries within rural and agricultural communities, customized to the Southwest Region. This brief descriptive report highlights the process by which strategic partners collaborated to conduct a regional agricultural medicine course, such that other organizations interested in offering a similar training might gain insight to best practices from our experience.